Preparation of Pd–B/palygorskite amorphous catalyst for the selective hydrogenation of o ‐chloronitrobenzene to o ‐chloroaniline. (1st June 2016) - Wu, Mei; Xu, Ying; Jang, Jinlong; Ju, Jingxi; Zeng, Qingyun; Duanmu, Chuansong; Gu, Xu
Abstract : Pd–B amorphous alloy was successfully supported on the surface of natural nanoclay palygorskite (PAL) via a simple chemical reduction method. Compared with the conventional supported Pd catalyst, the Pd–B/PAL amorphous catalyst possessed the ultra‐high selectivity (100%) to o ‐chloroaniline ( o ‐CAN) in the hydrogenation of o ‐chloronitrobenzene ( o ‐CNB) to o ‐CAN and avoided the dechlorination of o ‐CNB. XPS analysis results indicated that PAL support could reduce the electron density of Pd atoms and suppressed the hydrogenolysis of C–Cl bond. Meanwhile, the Pd–B/PAL amorphous catalyst exhibited a good stability and is a prospective catalyst for the selective hydrogenation of CNB to CAN.